KERJASAMA INDONESIA DENGAN WORLD WIDE FUND FOR NATURE (WWF) DALAM MENDORONG SUMBER DAYA ALAM BERKELANJUTAN PADA PROGRAM HEART OF BORNEO PERIODE 2012-2015 - Juwandi, - (2018)
The HoB Initiative is the only cross-border conservation cooperation between the governments of Indonesia, Brunei, and Malaysia, which is aim to manage cross-border areas, manage protected areas, manage sustainable natural resources, develop ecotourism, and improve human capacity based on sustainable development principles , On the management of the initiative in the territory of Indonesia, WWF is the only non-state actor involved in the HoB Kelompok Kerja (Pokja) structure established by the Government of Indonesia based on Forestry Ministerial Decree No. 382 / menhut-II / 2011 the National Working Group HoB Program. In achieving the sustainable development objectives of the HoB initiative, the study found that there are several implementations of the Indonesian Cooperation Program with WWF in Promoting Sustainable Natural Resources at the Heart of Borneo Program for the period 2012-2015, including ongoing funding, assisting local governments in developing conservation districts , building green business networks, and enhancing and improving human resource capacity through collaboration with local initiatives